The HILDA complex coordinates a conditional switch in the 3'-untranslated region of the VEGFA mRNA. - Peng Yao; Alka A Potdar; Partho Sarothi Ray; Sandeepa M Eswarappa; Andrew C Flagg; Belinda Willard; Paul L Fox (PLoS Biology, 2013)
Cell regulatory circuits integrate diverse, and sometimes conflicting, environmental cues to generate appropriate, condition-dependent responses. Here, we elucidate the components and mechanisms driving a protein-directed RNA switch in the 3'UTR of vascular endothelial growth factor (VEGF)-A. We describe a novel HILDA (hypoxia-inducible hnRNP L-DRBP76-hnRNP A2/B1) complex that coordinates a three-element RNA switch, enabling VEGFA mRNA translation during combined hypoxia and inflammation. In addition to binding the CA-rich element (CARE), heterogeneous nuclear ribonucleoprotein (hnRNP) L regulates switch assembly and function. hnRNP L undergoes two previously unrecognized, condition-dependent posttranslational modifications: IFN-γ induces prolyl hydroxylation and von Hippel-Lindau (VHL)-mediated proteasomal degradation, whereas hypoxia stimulates hnRNP L phosphorylation at Tyr(359), inducing binding to hnRNP A2/B1, which stabilizes the protein. Also, phospho-hnRNP L recruits DRBP76 (double-stranded RNA binding protein 76) to the 3'UTR, where it binds an adjacent AU-rich stem-loop (AUSL) element, "flipping" the RNA switch by disrupting the GAIT (interferon-gamma-activated inhibitor of translation) element, preventing GAIT complex binding, and driving robust VEGFA mRNA translation. The signal-dependent, HILDA complex coordinates the function of a trio of neighboring RNA elements, thereby regulating translation of VEGFA and potentially other mRNA targets. The VEGFA RNA switch might function to ensure appropriate angiogenesis and tissue oxygenation during conflicting signals from combined inflammation and hypoxia. We propose the VEGFA RNA switch as an archetype for signal-activated, protein-directed, multi-element RNA switches that regulate posttranscriptional gene expression in complex environments.